A better programme for mentoring youths - Atuya, Caleb A. (Technical Centre for Agricultural and Rural Cooperation, 2019)
The Kenya Livestock Producers Association (KLPA) is working to institutionalise the experience capitalization approach in its M&E department by developing specific Terms of Reference (TOR) which will be used in the ongoing and subsequent projects that KLPA is engaged in. KLPA is an apex farmer organisation, formed in 2004 with the aim of helping farmers with market linkages, conducting farmer trainings on various value chains, and lobbying and advocacy. In 2017, KLPA partnered with Mkulima Faida Africa and started the DIGIFARM project. The aim is to help young people in agricultural value chains share their success stories and encourage more youths to create value in the sector